(untitled) (Global Journal of Medical Research, 2023)
Due to the lack of a clear distinction between mentally-driven psychiatric symptoms and neurologically-driven psychiatric symptoms determining which patients would best be treated with psychotherapy which patients would best be treated with pharmacotherapy and which patients would best be treated with both is a challenge that every behavioral health clinician faces In an effort to overcome this challenge this article will discuss the anatomical and functional relationship between the mind and the brain as it relates to the various treatment options that are currently available and introduce a groundbreaking new paradigm that is destined to transform the treatment of mental illness from a symptom-based practice to a pathology-based practice